Atalanta: Militär gegen Piraterie - Gerstenberger, Heide (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2011)
The author discusses the causes, the special forms and the consequences of piracy in the coastal waters of Somalia. She debates the reasons for the decision of the European Union to launch a military operation against piracy. In spite of the fact that the German constitution prohibits the use of armed forces for the prevention of criminal acts German naval forces are taking part in the European military operation „Atalanta“.